ANALISIS KINERJA FITUR AUGMENTED REALITY DI KOTA TUA SURABAYA BERBASIS WEB XR - Muhammad Adi Stiyawan; Citra Devi Murdaningtyas; Widi Sarinastiti (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Existing AR-based cultural heritage solutions often rely on platform-specific apps or hardware requirements, limiting accessibility and scalability. This study presents a novel approach by developing an AR navigation system based on WebXR, utilizing marker-based tracking with Immersal SDK and 3D visualization through Mattercraft. The system delivers real-time historical information and directional guidance directly via mobile browsers, eliminating the need for additional installations. While previous research has explored AR for cultural tourism, this work is unique in offering a cross-platform, browser-based solution that enhances user accessibility across both iOS and Android devices. Functional testing revealed that iOS devices, especially older models with lower RAM, showed better performance compared to Android, indicating the significant role of device hardware in AR functionality. The system was effective up to 50 meters and at angles below 50°, with optimal lighting improving display quality. This study fills a critical gap in the AR field by demonstrating how WebXR can offer an accessible, scalable, and immersive